Implementation of retail gasoline sales in terms of Islamic business ethics (Study in Gading Cempaka District, Bengkulu City) - Faisal Faisal (Digital Business: Tren Bisnis Masa Depan, 2022)
Study it was found that (1) the implementation of retail gasoline There are two issues studied in this thesis, namely: (1) How is the implementation of retail gasoline sales in Gading Cempaka District, Bengkulu City (2) How is retail gasoline sales in Gading Cempaka District, Bengkulu City in terms of Islamic business ethics. The purpose of this study was to find out how retail gasoline sales are implemented in terms of Islamic business ethics in Gading Cempaka District, Bengkulu City. To reveal this problem in depth and thoroughly, the researcher uses a qualitative descriptive method which is useful for providing information, facts about the implementation of retail gasoline sales in Gading Cempaka District, Bengkulu City. Then the data is described, analyzed and discussed to answer these problems. From the results of this sales in Gading Cempaka District, Bengkulu City still violates Presidential Decree 15 of 2012. (2) Retail gasoline sales in Gading Cempaka District, Bengkulu City are not in accordance with Islamic business ethics because retail gasoline sellers do not understand and apply Islamic Business Ethics.